A tale of two frames: Exploring the role of framing in the use discontinuance of volitionally adopted technology. (28th June 2021) - Soliman, Wael; Tuunainen, Virpi Kristiina
Abstract: The discontinuance of volitional IS (i.e., information systems adopted, used and discontinued at will) has recently attracted remarkable attention from academics and practitioners alike. However, most research to date has been ahistorical. Ignoring the temporal progression can be problematic when the phenomenon under investigation is dynamic and evolving. To balance this, we adopt a stage modelling approach to understand the process ending with the technology use being discontinued by users of a popular crowdsourcing platform. Two questions guided our investigation: (1) Why do users discontinue using an IS they have volitionally adopted and used? (2) How does IS discontinuance occur over time in such context? We develop a stage model demonstrating that five stages are critical in understanding IS discontinuance: IS framing, goal pursuit, frame disruption, dormancy and quitting, after which possible switching denotes a new cycle. Furthermore, we identify two frames that help us understand why different users interpret and evaluate the technology differently – namely, the gain frame and the hedonic frame. On one hand, a gain frame is linked to the goal of improving one's resources and thus directs the user's attention to the technology's instrumental value. On the other hand, a hedonic frame is linked to the goal of having fun and thus directs the user's attention to the technology's enjoyment value. But, most importantly, we show that the technology's use lifecycle as a whole from initial use to discontinuance is shaped and guided by the user's dominant frame. Our insights elicit a number of important theoretical and practical implications.